Opening a new era of investigating unreachable cliff flora using smart UAVs. Issue 4 (30th June 2021) - Zhou, Hui; Zhu, Jiaxing; Li, Jiaxiang; Xu, Yongfu; Li, Qian; Yan, Enping; Zhao, Shaohua; Xiong, Yujiu; Mo, Dengkui
Abstract: Cliff ecosystems are considered the 'Last Unknown' because cliffs may host ancient and unique species that are located in extremely hostile environments and are difficult to reach. However, comprehensive and systematic information and databases of cliff flora are unavailable; and obtaining information on these undisturbed ecosystems and cliff flora is fundamental and is of high priority for botanists. We present the first systematically sampled expert‐verified checklist of cliff flora from the ground to the top of cliffs in these harsh environments based on high‐resolution visible imagery captured with close‐range photogrammetry by a smart remote‐controlled unmanned aerial system (UAS). Using approximately 9200 records retrieved from high‐resolution images of 197 cliffs in the Wulingyuan global cultural heritage area, a mid‐subtropical region in China, we identified 267 vascular plant species, 140 genera and 58 families, excluding herbaceous plants. The maximum diversity was attributable to a few dominant families and genera, and most of the genera and families were represented by only a few species. Our findings highlight the unique floristic patterns as well as morphology on these cliffs that warrant further study and the potential for the use of a smart UAS to investigate cliff flora at large and global scales. Abstract : Cliff flora is one of the least understood vegetation types and cliff ecosystems are considered the 'Last Unknown' due to inaccessibility to humans. However, obtaining information on these undisturbed ecosystems and cliff flora is fundamental and is of high priority for ecologists and conservationists alike. We proposed an innovative method based on high‐resolution visible imagery captured with close‐range photogrammetry by a smart remote‐controlled unmanned aerial system (UAS), and present the first systematically sampled expert‐verified checklist of the cliff flora from the ground to the top of cliffs in these harsh environments. Our findings highlight the unique floristic patterns as well as morphology on these cliffs that warrant further study, and the potential for the use of smart UAS to investigate cliff flora and accelerate ecological research in the 'Last Unknown' globally.